2022
DOI: 10.1186/s43162-022-00141-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of interferon gamma inducible protein-10, monocyte chemoattractant protein-1, macrophage inflammatory protein-1 alpha, interleukin-6, and rs12252 single nucleotide polymorphism of interferon-induced transmembrane protein-3 gene with the severity of COVID-19 infection

Abstract: Background Evaluating the serum levels of IP-10, MCP-1, MIP-1α, and IL-6 and genotyping of rs12252 SNP of IFITM3 gene among different categories of COVID-19 patients might aid in understanding the pathogenesis of COVID-19 and contribute to developing disease-specific biomarkers and therapeutic strategies. Methods This is a cross-sectional study involving a total of 84 COVID-19 patients confirmed by positive RT-PCR and 28 healthy controls. COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…1 On the other hand, other studies compared patients admitted to the ICU with those in the wards or those with different clinical pictures. 16,17 According to these results, IP-10 may be a good biomarker for predicting the progression of the COVID-19 patient newly admitted to the hospital. Still, it may not be a good biomarker for the COVID patients followed in the ICU.…”
Section: Discussionmentioning
confidence: 93%
“…1 On the other hand, other studies compared patients admitted to the ICU with those in the wards or those with different clinical pictures. 16,17 According to these results, IP-10 may be a good biomarker for predicting the progression of the COVID-19 patient newly admitted to the hospital. Still, it may not be a good biomarker for the COVID patients followed in the ICU.…”
Section: Discussionmentioning
confidence: 93%
“…This phenomenon has been considered an important contributor to ARDS and MODS in COVID-19 patients [ 3 ]. It has been reported that the levels of IL-6, interleukin-2 (IL-2), interleukin-7 (IL-7), IL-10, tumor necrosis factor-alpha (TNF-α), granulocyte colony-stimulating factor (G-CSF), interferon gamma induced protein (IP-10), monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein-1 alpha (MIP-1α) were significantly higher in COVID-19 patients [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IFNγ concentrations were positively correlated with LDH levels. Interestingly, several studies have found that IFNγ-induced protein 10 (IP-10), together with CRP, is a relevant marker of mortality in COVID-19 [ 53 , 54 ]. At the same time, reduced serum IFNλ2 levels have been associated with greater disease severity [ 55 ], suggesting low antiviral activity and SARS-CoV-2 persistence.…”
Section: Discussionmentioning
confidence: 99%